Development of Metalinguistic Awareness for Reading Comprehension in Spanish as a Second Language - Quispe-Morales, Rolando Alfredo (2022)
Objective. The research is the product of an experience carried out to verify the effect produced by the development of metalinguistic awareness in the improvement of reading comprehension in Spanish, as a second language, in primary level students of a bilingual intercultural education institution. Method. The study has a quantitative and quasi-experimental design, with a pretest and post-test in a control group and an experimental group. The sample consisted of 50 schoolchildren, 25 students in the control group, and 25 in the experimental group, from classrooms “A” and “B”. Data collection was performed through an objective test, with the corresponding validity and reliability test. The Mann Whitney and Wilcoxon U statisticians were used for the hypothesis test. Results. The main finding shows that, in the pre-test, the dependent variable and its dimensions presented a level of sig.> 0.05. Once the process was concluded and the post-test was applied, it presented a level of sig. <0.05, observing a difference in favor of the experimental group. Conclusions. The analysis of the statistical values obtained allows us to conclude that the development of metalinguistic awareness produces significant effects on reading comprehension at a literal, inferential, and critical level in Spanish as a second language in primary school students. Therefore, it is recommended to deepen the study in different samples to generalize the development of metalinguistic awareness as a proposal to improve reading comprehension in Spanish as a second language.